The Acid Catalyzed Reaction of α-Pinene Over Y-Zeolite - Nanik Wijayati; Harno Dwi Pranowo; Jumina Jumina; Triyono Triyono (Indonesian Journal of Chemistry, 2013)
The hydration of α-pinene has been studied in the presence of Y-zeolite (Si/Al = 2.89) as a solid acid catalyst. The reaction was performed in batch reactor in isopropyl alcohol at various temperature and reaction time with magnetic stirrer. The acid catalyst hydration reaction of a-pinene yields a complex mixture of monoterpenes, alcohols and hydrocarbons. The selectivity of α-terpineol (the monocyclic alcohol) as main product was 59.20% with a conversion of 83.83% and the non alcoholic as the isomerization co-product as 30% after 60 min at 65 °C. The conversion and selectivity to α-terpineol increase significantly with in increase in temperature and reaction times.